Copper-Mediated Fluorination of Aryl Iodides - Fier, Patrick S.; Hartwig, John F. (Journal of the American Chemical Society, 2012)
The synthesis of aryl fluorides has been studied intensively because of the importance of aryl fluorides in pharmaceuticals, agrochemicals, and materials. The stability, reactivity, and biological properties of aryl fluorides can be distinct from those of the corresponding arenes. Methods for the synthesis of aryl fluorides, however, are limited. We report the conversion of a diverse set of aryl iodides to the corresponding aryl fluorides. This reaction occurs with a cationic copper reagent and silver fluoride. Preliminary results suggest this reaction is enabled by a facile reductive elimination from a cationic arylcopper(III) fluoride.